Implementation of a financially incentivized weight loss competition into an already established employee wellness program - Andrew M. Schramm; Kristen L. DiDonato; Justin R. May; D. Matthew Hartwig (University of Minnesota Libraries Publishing, 2014)
Objective: To assess improvement in clinical outcomes and patient satisfaction of a financially incentivized weight loss competition adjunct to a currently established pharmacist-directed employee wellness program. Design: Retrospective, cohort, pilot study Setting: 6 independent community pharmacy chain locations, two long-term care pharmacies, and a pharmacy corporate office in northwest and central Missouri, from January 2013 to April 2013. Participants: 24 benefit-eligible patients employed by the self- insured pharmacy chain. Intervention: A financially incentivized weight loss competition focusing on healthy lifestyle practices was implemented at nine pharmacy locations over an eight week period. Main outcome measure(s): Change from baseline in mean total cholesterol, serum triglycerides, high-density lipoprotein cholesterol (HDL-C), low-density lipoprotein cholesterol (LDL-C), systolic blood pressure (SBP), diastolic blood pressure (DBP), weight, and body mass index (BMI). Patient satisfaction was also assessed after completion. Results:24 patients completed the competition. The average weight loss among all participants was 10 ± 7.3 pounds. A mean decrease in serum triglycerides was significant at 36.9 mg/dL per participant (p Conclusion: The implementation of a financially incentivized weight loss competition provided significant short-term weight loss to a patient population that was already enrolled in an established pharmacist-directed employee wellness program and had not shown clinical improvement prior to the intervention. Overall the patients were satisfied, felt healthier, and agreed to continue following the recommendations of the program.   Type: Original Research